How Tía Lola came to visit stay - Alvarez, Julia. (Knopf : Distributed by Random House, 2001)
Although ten-year-old Miguel is at first embarrassed by his colorful great aunt, Tia Lola, when she comes to Vermont from the Dominican Republic to stay with his mother, his sister, and him after his parents' divorce, he learns to love her.